Uji Efektifitas Pestisida Nabati Biji Mimba (Azadirachta indica A. Juss) terhadap Hama yang Menyerang Selada Merah (Lactuca sativa var. acephala) - Raja Malem Kata Keliat; A.A. Ayu Agung Sri Sunari; Ni Nengah Darmiati (Fakultas Pertanian, Universitas Udayana, 2024)
The purpose of this study is to determine the type (species) of pests that attack red lettuce plants (Lactuca sativa var. acephala), knowing the effect of neem seed vegetable pesticide application in controlling pests on red lettuce and knowing the concentration of neem seed vegetable pesticides that are most effective in controlling pests on red lettuce plants. The research was conducted from May to June 2023 on the land of Biaung Village, Pemanis Hamlet, Penebel District, Tabanan Regency which is located at 8°-24'33-5